General principles of criminal offenses skills in business - Кісілюк, Е.М; Процюк, О.В (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2015)
The article analyzes the General framework of qualification of criminal offences in the sphere of economic activity in the part of the peculiarities of the establishment of characteristics of the object, the objective side of the subject and subjective components of crime. The descriptions of criminal offenses in the sphere of economic activity the author emphasizes that it is necessary to take into account the trend of modern economic crime to the proliferation not only in economics but also in government and politics, which involves the scope of their interests in state machine enters into the sphere of power and government. Noted this relationship caused not every time and therefore the authority of state and local government advocates an optional direct object and when combined with a major direct object, perfect in need of total training. In this case indicates that the current state of Ukraine’s economy has not yet fully meet the reference sample efficient economic models, operating in conditions of free competition and the rule of law. Under these conditions, the legislator has failed to develop a perfect legal framework to protect the economy against criminal attacks

У статті проаналізовано загальні засади кваліфікації кримінальних правопорушень у сфері господарської діяльності в частині особливостей встановлення ознак об’єкта, об’єктивної сторони, суб’єкта та суб’єктивної сторони складу злочинів.
ЗАГАЛЬНІ ЗАСАДИ КВАЛІФІКАЦІЇ КРИМІНАЛЬНИХ ПРАВОПОРУШЕНЬ У СФЕРІ ГОСПОДАРСЬКОЇ ДІЯЛЬНОСТІ
Keywords: qualification; business; economics; criminal offences; crime; public relations; the subject of the crime; consequences; кваліфікація; господарська діяльність; економіка; кримінальні правопорушення; злочини; суспільні відносини; предмет злочину; наслідки